2022
DOI: 10.3389/fonc.2022.876264
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Combined Radiomics and Clinical Features as Imaging Biomarkers for Prediction of Visceral Pleural Invasion in Lung Adenocarcinoma

Abstract: ObjectivesTo develop and validate a nomogram model based on radiomics features for preoperative prediction of visceral pleural invasion (VPI) in patients with lung adenocarcinoma.MethodsA total of 659 patients with surgically pathologically confirmed lung adenocarcinoma underwent CT examination. All cases were divided into a training cohort (n = 466) and a validation cohort (n = 193). CT features were analyzed by two chest radiologists. CT radiomics features were extracted from CT images. LASSO regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Eventually, 10 optimal quantitative radiomic features were extracted. This study covered first-to high-order texture features which is partially consistent with a previous study by Wei et al, 28 suggesting some similarities between the two studies regarding texture features, but not in agreement with the study by Zha et al 15 According to our study, the model combination with radiomic and clinical features is more effective. Due to the difficulty in delineating peritumoral ROI for the reason of the proximity of the tumor to the pleura, we only annotated the interior VOI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Eventually, 10 optimal quantitative radiomic features were extracted. This study covered first-to high-order texture features which is partially consistent with a previous study by Wei et al, 28 suggesting some similarities between the two studies regarding texture features, but not in agreement with the study by Zha et al 15 According to our study, the model combination with radiomic and clinical features is more effective. Due to the difficulty in delineating peritumoral ROI for the reason of the proximity of the tumor to the pleura, we only annotated the interior VOI.…”
Section: Discussionsupporting
confidence: 90%
“…The studies by Yuan et al 14 and Zha et al 15 attempted to derive automated quantitative imaging features to reach a noninvasive preoperative diagnosis for lung cancer with VPI hybridizing pure‐solid and solid lung lesions. Few studies have investigated radiomic signatures in only part‐solid lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with histogram and texture analysis, radiomics provide more high-dimensional and otherwise unrecognizable in-depth information and can comprehensively capture the characteristics of tumor heterogeneity in images. At present, there are only two researches on the use of radiomics to predict VPI ( 36 , 37 ). Yuan et al ( 36 ) analyzed the CT imaging characteristics of 327 cases of early lung adenocarcinoma with a maximum diameter ≤3 cm and found that several imaging characteristics (e.g., percentile 10%, WavEnLLS_2, and S-0_1SumAverage) reflected tumor heterogeneity and that differed significantly between the VPI positive and negative groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the radiomics model was constructed based on only the tumor and not the combined CT morphological features. Zha et al ( 37 ) excluded the pure GGN type and included a total of 659 cases of IA lung adenocarcinoma. Based on the tumor imaging features and CT signs, a comprehensive prediction model of VPI was constructed, with an AUC value of 0.89 in the training set and 0.88 in the internal verification set.…”
Section: Discussionmentioning
confidence: 99%
“…The 10-fold cross-testing was used to identify the optimal regularization parameter λ. The radiomics score (R-score) was calculated based on the fitting formula of the radiomics signature for all patients ( 17 ). The predictive accuracy of the radiomics signature was evaluated in both sets.…”
Section: Methodsmentioning
confidence: 99%